Differential Response to Injury in Fetal and Adolescent Sheep Hearts in the Immediate Post-myocardial Infarction Period - Lock, Mitchell C.; Darby, Jack R. T.; Soo, Jia Yin; Brooks, Doug A.; Perumal, Sunthara Rajan; Selvanayagam, Joseph B.; Seed, Mike; Macgowan, Christopher K.; Porrello, Enzo R.; Tellam, Ross L.; Morrison, Janna L. (Frontiers in Physiology, 2019)
Aims: Characterising the response to myocardial infarction in the regenerative sheep fetus heart compared to the postnatal non-regenerative adolescent heart may reveal key morphological and molecular differences that equate to the response to myocardial infarction in humans. We hypothesised that the immediate response to injury in a) infarct compared with sham, and b) infarct, border and remote tissue, in the fetal sheep heart would be fundamentally different to the adolescent, allowing for repair after damage. Methods: We used a sheep model of myocardial infarction induced by ligating the left anterior descending coronary artery. Surgery was performed on fetuses (105 days) and adolescent sheep (6 months). Sheep were randomly separated into Myocardial infarction (n=5) or Sham (n=5) surgery groups at both ages. We used magnetic resonance imaging (MRI), histological/immunohistochemical staining and qRT-PCR to assess the morphological and molecular differences between the different age groups in response to infarction. Results: MRI showed no difference in fetuses for key functional parameters; however there was a significant decrease in left ventricular ejection fraction and cardiac output in the adolescent sheep heart at three days post infarction. There was no significant difference in functional parameters between MRI sessions at Day 0 and Day 3 after surgery. Expression of genes involved in glucose transport and fatty acid metabolism, inflammatory cytokines as well as growth factors and cell cycle regulators remained largely unchanged in the infarcted compared to sham ventricular tissue in the fetus, but were significantly dysregulated in the adolescent sheep. Different cardiac tissue region-specific gene expression profiles were observed between the fetal and adolescent sheep. Conclusion: Fetuses demonstrated a resistance to cardiac damage not observed in the adolescent animals. The manipulation of specific gene expression profiles to a fetal-like state may provide a therapeutic strategy to treat patients following an infarction.